ANALISIS KUALITAS PELAYANAN BUS TRANS JATENG SOLO WONOGIRI MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Subekti, Tiara Meilania; Hidayati, Lydia Novitriana Nur; Yulianto, Budi (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2025)
The Solo Wonogiri corridor is one of the seven agglomeration areas served by the Trans Jateng Bus and is widely utilized by the public. This service system adopts a buy-the-service scheme based on six Minimum Service Standard (SPM) indicators: comfort, security, safety, affordability, equality, and orderliness. To support service quality improvement, an evaluation of user perceptions is necessary as a foundation for providing policy recommendations to the government. This study assesses the service quality of the Trans Jateng Bus on the Solo Wonogiri route using the Importance Performance Analysis (IPA) method across 14 service attributes. The IPA method categorizes attributes into four quadrants based on their level of importance and passenger satisfaction to identify which aspects should be maintained or improved. The analysis results indicate an average conformity level of 94%, reflecting a very satisfactory service quality, although several attributes still require improvement. Among the 14 attributes, two are positioned in quadrant I (top priority for improvement), five in quadrant II (should be maintained), two in quadrant III (low priority), and five in quadrant IV (excessive). These findings can serve as a reference for formulating strategies to enhance public transportation services in the Solo Wonogiri corridor.